Marine debris on selected public beaches in Kuching, Bintulu and Miri, Sarawak - Julyus, Melvin Mobilik (Universiti Malaysia Sarawak, (UNIMAS), 2008)
Sarawak being the largest state in Malaysia with approximately 800 kilometers of coastline facing the South China Sea stretching from Tg. Dato, Sematan to Merapok, Lawas, represents a complex and dynamic systems both in terms of human activities and in terms of their biophysical conditions. However some beaches in Sarawak are suffering serious pollution due to either natural cause or human impact. Approximately one kilometer stretch has been survey and identify of marine debris landed on shoreline at four public beaches namely Pandan beach (Lundu), Pasir Pandak (Santubong), Tg. Batu beach (Bintulu) and Tg. Lobang (Mini) In this study, interviews have been conducted with local authorities and 32 individual questionnaires has been administered. A total of 7,199 items or 1,800 items/km of survey site was collected from the 4 km surveyed in this study and weighed at 304 kg or 76 kg/km. Pasir Pandak (3,356 items/km or 153 kg/km) received substantially greater quantities of debris compare to Pandan, Tg. Lobang and Tg. Batu beaches. The most numerous items on all four study sites were those made of plastic and paper where 72.47 percent of marine debris originated from Malaysia. Respondents were satisfied with the beach environment (61.8%) and 85.3 percent respondents were willing to be involved in beach clean-up exercise suggesting that most people acknowledge the problems of rubbish on beaches and they were willing to make contribution to maintain the level of cleanliness. Overall respondents were more concerned on the public facilities rather then the beach environment and cleanliness. The data obtained in this study were considered as preliminary data and limited to only four theses beaches. They were just 'snap-shots' of marine debris problems in those selected study sites. It is necessary to continue this study in future in order to make recommendation for strategies in marine debris management.